Remembering the Past, Building the Future: Miri’s WWII Memorial and the Resilience of the Human Spirit - Justin Dit, Terry (Curtin Malaysia, 2025)
Memorials are more than just stone and steel; they are testaments to the human spirit. We build them to honour the past, to learn from history, and to shape a better future. These structures serve as powerful reminders of significant people, events, and sacrifices, ensuring their legacies endure despite the passage of time. They offer tangible connections to the past, transforming abstract historical narratives into palpable experiences. For communities grappling with loss and trauma, memorials provide a crucial space for collective healing, a place where grief can be shared and solace found.